Assessment Practices of Teachers Implementing the Philippines and Singapore Elementary Mathematics Curriculum - Villon, Joy Therese Lomod (Jurnal Pendidikan Progresif, 2023)
This study compared the assessment practices of Filipino teachers in public schools implementing the national elementary mathematics curriculum with those in private schools implementing the Singapore mathematics curriculum in the Philippines,and provide inputs to the Philippine Elementary Mathematics curriculum based on the findings.  The researcher used document analysis, interviews, and classroom observations determine their assessment practices of the participants.Triangulation was done to ensure data validity to fulfill the study's purpose. The results reveal that there are similarities and differences in the assessment practices of elementary teachers using Philippines and Singapore Elementary Mathematics curriclum. However, the study did not test if Filipino elementary learners differ in their performance in the national assessments given to all learners in public and private schools. Hence, the study recommended that future analysis be made on how Filipino elementary learners differ in their performance in mathematics, considering their differences in the curriculum they are exposed to. Keywords: assessment practices, elementary mathematics teachers, Philippine elementary mathematics curriculum, Singapore elementary mathematics curriculum